Hubungan antara Pemakaian Alat Kontrasepsi Dalam Rahim (AKDR) dan Kejadian Kanker Serviks di RSUD Dr. Moewardi - Octava Prima Arta; Rustam Sunaryo; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: One government program in an effort to deal with the increasing population is a national family planning program, in particular by the use of contraceptives. Intrauterine Device (IUD) is the one form of contraception is widely used in society but still not much information about the correct usage and side effects. Bacterial or viral infection is one of the side effects of IUD use, including Human Papilloma Virus (HPV) infection, the virus that causes cervical cancer. The purpose of this study to determine the incidence rate of cervical cancer associated with IUD use. Research Methods: This type of case-control study. Sample of this study were gynecologic cancer patients with a total sample of 60 people. Measuring instrument used was a validated questionnaire, and performed data analysis with multiple logistic regression analysis. Result: Found a statistically significant association between IUD users with the incidence of cervical cancer. IUD users will experience cervical cancer 12 times compared to non-IUD users (p = 0,001, OR=12,70). Conclusion: Based on research IUD users will experience a risk for cervical cancer 12,7 times higher than those not using an IUD. Keyword: Intrauterine Device, cervical cancer